Effects of the ZnO buffer layer and Al proportion on AZO film properties - 隋成华 刘彬 徐天宁 鄢波 魏高尧 (Optoelectronics letters, 2012)
To evaluate the influence of the ZnO buffer layer and A1 proportion on the properties of ZnO： A1 （AZO）/ZnO bi-layer films, a series of AZO/ZnO films are deposited on the quartz substrates by electron beam evaporation. The X-ray diffraction measurement shows that the crystal quality of the films is improved with the increase of the film thickness. The electrical properties of the films are investigated. The carrier concentration and Hall mobility both increase with the increase of buffer layer thickness. However, the resistivity reaches the lowest at about 50 nm-thick buffer layer. The lowest resistivity and the maximum Hall mobility are both obtained at 1 wt% Al concentration. But the optical transmittance of all the films is greater than 80% regardless of the buffer layer thickness with A1 concentration lower than 5 wt% in the visible region.